P80 Coming and Going: COPD Patients' Experiences of Hospital Admission and Discharge. (19th November 2012) - Hodson, M; Andrews, S; Walker, S; Roberts, M
Abstract : Background Chronic Obstructive Pulmonary Disease (COPD) is a major cause of emergency hospitalisation in the UK. Identifying the principal decisions of seeking admission to hospital and subsequent experiential aspects for the admission and discharge process make it possible to benchmark future quality service provision for COPD patients. Aim: Part of a larger study about COPD this aspect of the research aimed to identify patients' experiences of being hospitalised with COPD. The focus of this presentation is about patient-reported experiences of making the decision to go to hospital and later, their subsequent discharge from hospital. Method: Nineteen patients with recent acute hospital care for a COPD related illness or exacerbation were interviewed face-to-face. Recent was defined as admission within the last 3 months prior to the interview. The interviews were conducted in patients' homes. The sample comprised 12 males (63%), 7 (37%) females. The mean age for males and females was 70 years. The data was coded and grouped into 5 categories. The findings for the categories: "Going to hospital" and "Discharge from hospital" are presented. Findings: COPD patients have much experience in managing an exacerbation of their condition and can recognise significant changes in their health status requiring urgent hospitalisation. The findings for "Going to hospital" include: who patients rely on to make the decision, how the decision is made/or avoided and their emotive experiences of going to hospital. Patient experiences around "Discharge from hospital" include: consultation, confusion, timeliness and (lack of) streamlining in the discharge process. Patient narratives will be presented. Conclusion: Decision-making about going to hospital and the subsequent discharge process can be viewed as the beginning and end points in the hospitalisation journey for COPD patients. Patient experiences about these points in the journey give key insights into decision making, quality care and identify benchmarks for future reviews of service provision to COPD patients.